A precursor method for the synthesis of new Ce(iv) MOFs with reactive tetracarboxylate linkers. Issue 8 (13th December 2017) - Smolders, Simon; Struyf, Arnaud; Reinsch, Helge; Bueken, Bart; Rhauderwiek, Timo; Mintrop, Luise; Kurz, Philipp; Stock, Norbert; De Vos, Dirk E.
Abstract : A new precursor method using glycinate/nitrate capped Ce6 clusters enables the synthesis of Ce(iv ) MOFs with reactive linkers. Abstract : A precursor method has been developed to synthesize Ce(iv ) MOFs that could not be prepared directly from Ce(iv ) salts. Starting from Ce6 clusters, two Ce-UiO-66 analogues and four tetracarboxylate-based Ce(iv ) MOFs could be synthesized. The applied method facilitates framework formation by evading reactive individual Ce(iv )-ions thereby paving the way for further development of Ce-MOFs.